PENGEMBANGAN MEDIA PEMBELAJARAN BERBENTUK MIND MAP MENGGUNAKAN SOFTWARE FREEMIND PADA MATA PELAJARAN EKONOMI POKOK BAHASAN KEBUTUHAN MANUSIA KELAS X DI SMA NEGERI 4 PALEMBANG - Aulia Aulia; M. Djahir Basir; Rusmin AR (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2014)
This development research aims to produce learning media in the form of mind map using freemind software on economic subjects subject of human need for students of class X SMA Negeri 4 Palembang. The research method used is development method (Development Research) A. Design development using Akker development model. The development steps are the needs analysis phase, the design phase and the revision and evaluation phase, the revision and evaluation phase of the researcher refers to the Tessmer formative evaluation model with the steps are self evaluation stage, Expert review stage and one to one, small group stage and stage test field. In the self evaluation stage, the researcher analyzed the learning materials and the characteristics of the students in operating the computer, followed by designing instructional media from paper based form to computer based which in this stage produces prototype 1. The result of Expert review stage on expert material obtained validation of 3.95% with good category, and the validation result with media expert is 4.20 with good category which means media is categorized valid media, then continued on one to one test on three students with observation result of 48% learners are seen actively using the learning media. in the small group stage obtained the results of observations of 80% with the active category, meaning that learning media are classified as practical or easy to use media, on the field test stage of this learning media has a potential effect on learning outcomes learners with the average learning outcome of 84 with categories high and n-score score of 0.56.